IMPLEMENTASI SISTEM PENGAMBILAN KEPUTUSAN UNTUK PEMETAAN PRIORITAS PEMBANGUNAN DAERAH DI KABUPATEN BOGOR - Khotib Arifai, Mukhamad; Hardiansyah; Ramdhani, Ichsan (Journal of Research and Publication Innovation, 2024)
Regional development is a key element in achieving community prosperity and sustainable economic growth. One district that reflects this diversity is Bogor Regency, which is located in West Java Province. Bogor Regency, with its large population, rapid dynamics of change, and diverse economic sectors, requires wise and systematic development planning. RPJMD is a strategic planning document used by local governments to formulate vision, mission and development goals in the medium term. The RPJMD usually covers a 5-year period and is the basis for preparing development plans and programs at the regional level. According to Bachrawi (2000) development must pay attention to many aspects. Mapping development priorities is a critical stage in this process, ensuring that limited resources are allocated to projects that will have the greatest positive impact on society. Mapping development priorities is a very important first step in this planning process. Development projects must be evaluated and ranked according to priority, taking into account social, economic, environmental and financial impacts. So, the regional government of Bogor Regency has tried to map out development priorities. AHP (Analytical Hierarchy Process) is a method used in multi-criteria decision making, developed by Thomas L. Saaty. This method allows decision makers to compare various criteria and alternatives, and produce priorities based on objective preferences. AHP is a powerful tool for helping humans make complex decisions by modeling a hierarchy of factors that influence decisions and combining them in a consistent comparison system. The aim of this research is to implement a decision making system using the Analytical Hierarchy Process (AHP) method for mapping regional development priorities in Bogor Regency.